Characteristics of unsteady flow around a vehicle affecting its high-speed stability during a dynamic steering action - Yoshihiro OKADA; Takahide NOUZAWA; Makoto TSUBOKURA; Takuji NAKASHIMA (Nihon Kikai Gakkai ronbunshu, 2014)
In order to clarify unsteady flow structure’s behavior that improves vehicle’s high-speed stability during steering input, on-road analysis was conducted. The analysis was conducted on two vehicles’ aerodynamic specifications which were produced by configuring two different shapes from a single vehicle. During high speed driving while steering input in sinusoidal waveform was being applied, these two vehicles were analyzed focusing on the relationships between dynamic movements, unsteady forces affecting on vehicle’s body surface and unsteady behavior of flow structure. As a result, it was clarified that there existed a unsteady behavior of flow structure that aerodynamically control to stabilize vehicle’s steering response motion in vertical and yawing direction. It was also clarified that this aerodynamic force that control to stabilize vehicle’s steering response motion was caused by behaviors of flow structure beside body just behind front tire which reduced and expand its vertical scale during high-speed driving with steering input. Furthermore, it was shown that this behavior of flow structure was caused by weakening vortex structure which came out and separated from the gap between the upper rear side of the front wheel and the front wheel arch.